2002
DOI: 10.1029/2001gl014225
|View full text |Cite
|
Sign up to set email alerts
|

Monsoonal characteristics revealed by intraseasonal variability of Sea Surface Temperature (SST) in the South China Sea (SCS)

Abstract: [1] Intraseasonal variability of SST in the SCS is examined. The results demonstrate that characteristics of intraseasonal SST variations in summer are remarkably different from those in winter. In summer, the spatial correlation pattern of intraseasonal SST perturbations is zonally distributed in the monsoon region. They are characterized by the northeastward propagation. In contrast, it appears to be localized in the SCS region without any propagating signal in winter. In addition, intraseasonal SST fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 11 publications
(14 reference statements)
0
15
0
1
Order By: Relevance
“…Existing research has shown that, although the SCS has a climatological warm pool structure [78,79], its SST has significant interannual variation [80], and the interannual variability of the basin-wide SST is different in winter and summer [81]. Through the atmospheric and ocean circulations [82,83], the El Niño and Southern Oscillation (ENSO) signal can affect the oceanic variability in the SCS.…”
Section: Air-sea Interactionmentioning
confidence: 99%
“…Existing research has shown that, although the SCS has a climatological warm pool structure [78,79], its SST has significant interannual variation [80], and the interannual variability of the basin-wide SST is different in winter and summer [81]. Through the atmospheric and ocean circulations [82,83], the El Niño and Southern Oscillation (ENSO) signal can affect the oceanic variability in the SCS.…”
Section: Air-sea Interactionmentioning
confidence: 99%
“…The SCS monsoons display significant intraseasonal variability with two dominant periods of 30-60 and 10-25 days ( Slingo, 2001;Mao and Chan, 2005), and pronounced interannual variability (Xie et al, 1998). The multi-scale characteristics of the SCS physical parameters, including the sea surface temperature (SST), as well as wind and sea surface height, have been widely discussed (Wang et al, 2000;Qu, 2001;Gao and Zhou, 2002;Wang et al, 2006;Rong et al, 2007;Zhuang et al, 2010). Subject to the multi-scale variability of the physical factors, ocean color in the SCS may also exhibit a multi-scale variability.…”
Section: Introductionmentioning
confidence: 99%
“…The quasi-biweekly and intraseasonal SST variability may be caused by atmospheric low-frequency forcing (e.g. Gao and Zhou, 2002;Xie et al, 2007;Li et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Gao and Zhou, 2002). In summer, SST intraseasonal variability is strong off southern Vietnam associated with the intraseasonal variability of an orographic wind jet (e.g.…”
Section: The Impacts Of Synoptic-scale and Low-frequency Sst Variabilmentioning
confidence: 99%